Acute liver failure impairs function and expression of breast cancer‐resistant protein (BCRP) at rat blood–brain barrier partly via ammonia‐ROS‐ERK1/2 activation. Issue 2 (30th May 2016) - Li, Ying; Zhang, Ji; Xu, Ping; Sun, Binbin; Zhong, Zeyu; Liu, Can; Ling, Zhaoli; Chen, Yang; Shu, Nan; Zhao, Kaijing; Liu, Li; Liu, Xiaodong
Abstract: We once reported that P‐glycoprotein (P‐GP) and multidrug resistance‐associated protein 2 (MRP2) were oppositely regulated at the blood–brain barrier (BBB) of thioacetamide‐induced acute liver failure (ALF) rats. This study aimed to investigate whether ALF affected function and expression of breast cancer‐resistant protein (BCRP) at the BBB of rats and the role of ammonia in the regulation. ALF rats were developed by intraperitoneal (i.p.) injection of thioacetamide (300 mg/kg) for 2 days. Hyperammonemic rats were developed by NH4 Ac (i.p. 4.5 mmol/kg). BCRP function and expression were measured by brain distribution of specific substrates (prazosin and methotrexate) and western blot, respectively. MDCK‐BCRP cells and primarily cultured rat brain microvessel endothelial cells (rBMECs) were employed to investigate possible mechanisms through which ammonia regulated BCRP function and expression. The results showed that both ALF and hyperammonemia significantly weakened function and expression of BCRP in the brain of rats. The function and expression of BCRP in MDCK‐BCRP cells and rBMECs were strikingly decreased after exposure to NH4 Cl and H2 O2, accompanied by remarkable increases in the levels of phosphorylated ERK1/2 and reactive oxygen species (ROS). The altered BCRP expression and function by ammonia and H2 O2 were restored by ROS scavenger N‐acetylcysteine and ERK1/2 inhibitor U0126. Markedly increased levels of ERK1/2 phosphorylation and ROS were found in the brains of ALF rats and hyperammonemic rats. All above results indicated ALF down‐regulated expression and function of BCRP at BBB of rats partly via hyperammonemia. Activation of ROS‐mediated ERK1/2 phosphorylation may be one of the reasons that ammonia impaired BCRP expression and function at the BBB. The present study showed that the expression and function of breast cancer resistant protein (BCRP) at blood‐brain barrier (BBB) of thioacetamide‐induced ALF rats were down‐regulated which partly attribute to hyperammonemia. Activation of ROS‐mediated ERK1/2 phosphorylation may be one of the reasons that ammonia suppressed BCRP expression and function. Impaired BCRP at BBB might enhanced pharmacological/toxic effects of corresponding substrates on CNS. Abstract : The present study showed that the expression and function of breast cancer resistant protein (BCRP) at blood‐brain barrier (BBB) of thioacetamide‐induced ALF rats were down‐regulated which partly attribute to hyperammonemia. Activation of ROS‐mediated ERK1/2 phosphorylation may be one of the reasons that ammonia suppressed BCRP expression and function. Impaired BCRP at BBB might enhanced pharmacological/toxic effects of corresponding substrates on CNS.